2020
DOI: 10.1108/jmd-05-2019-0183
|View full text |Cite
|
Sign up to set email alerts
|

When leader is morally corrupt: interplay of despotic leadership and self-concordance on moral emotions and bullying behavior

Abstract: PurposeThis study investigates despotic leadership (DL) as an antecedent to bullying behavior with a mediating role of moral emotions at work. Another aim is to study the moderating role of self-concordance to buffer the relationship between DL and arousal of moral emotions.Design/methodology/approachThe authors collected two-source (sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 86 publications
(116 reference statements)
0
54
0
Order By: Relevance
“…When employees treated unfairly by their leaders it will generate negative emotions among them such as anger, disgust which is the result of the corrupt leadership they will perform deviant behaviour and in return will also treat their peers negatively. So an effective leadership or ethical role modelling of a leader will help the employees to deal with the negative emotions very effectively (Syed et al, 2019). Thus, it will prepare the employees to behave courageously against the negative emotions of anger and disgust as anger is the feeling of displeasure having the varying adverse list of destructive consequences such as violence, aggression, bullying.…”
Section: ) the Mediating Role Of The Moral Emotions Between Leaders Ethical Role Modelling And Morally Courageous Behaviour Among Employementioning
confidence: 99%
See 1 more Smart Citation
“…When employees treated unfairly by their leaders it will generate negative emotions among them such as anger, disgust which is the result of the corrupt leadership they will perform deviant behaviour and in return will also treat their peers negatively. So an effective leadership or ethical role modelling of a leader will help the employees to deal with the negative emotions very effectively (Syed et al, 2019). Thus, it will prepare the employees to behave courageously against the negative emotions of anger and disgust as anger is the feeling of displeasure having the varying adverse list of destructive consequences such as violence, aggression, bullying.…”
Section: ) the Mediating Role Of The Moral Emotions Between Leaders Ethical Role Modelling And Morally Courageous Behaviour Among Employementioning
confidence: 99%
“…Thus, the study had provided insights into moral emotions and ethics but neglected the leader role modelling (Gabriel, Lindebaum, & Geddes, 2016). Another study by (Syed et al, 2019) studied the negative role of a leader and its effect on moral emotions and bullying behaviour among employees. The study explained what the effect on employee behaviour is if the leader is, morally corrupt So based upon the gaps defined in the previous studies the present study is going to explain how the hindrances of moral emotions can be controlled through the leader role modelling thus developing morally courageous behaviour among employees.…”
Section: Introductionmentioning
confidence: 99%
“…Fernet et al, 2010;Syed et al, 2020). For example, Syed et al (2020) regarded despotic leadership as an extrinsic aspect and demonstrated that employees with low-level self-concordance goal, relative to employees with high-level self-concordance goal, would produce more moral emotions in the face of despotic leadership. Sheldon and Elliot (1999) also suggested that employees who are pursuing low-level self-concordance goal focused more on the extrinsic aspects of work, while employees who are pursuing self-concordance goal paid more attention on the intrinsic aspects of work.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…, 2020). For example, Syed et al. (2020) regarded despotic leadership as an extrinsic aspect and demonstrated that employees with low-level self-concordance goal, relative to employees with high-level self-concordance goal, would produce more moral emotions in the face of despotic leadership.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Recent literature explores dark personality aspects in organisations, ( Schyns et al, 2019 ; Czarna and Zajas, 2020 ; Ray et al, 2020 ), career success ( Oflu et al, 2020 ) and leadership ( Van Scotter, 2019 ; Mackey et al, 2020 ; Syed et al, 2020 ). Spurk et al (2016) observed that narcissism as a dark personality trait is positively related to salary, Machiavellianism is positively related to leadership position, and career satisfaction while psychopathy is negatively related to career outcomes.…”
Section: Introductionmentioning
confidence: 99%